Knowledge and information management behaviour in the light of empirical studies among students - Świgoń, Marzena (Qualitative and Quantitative Methods in Libraries; Vol 2 No 3 (2013): September 2013 Issue, 2017)
The results of empirical studies in the field of Personal Knowledge and Information Management (PKIM) will be presented. PKIM is a humanistic and integrated approach of three concepts: Personal Information Management (PIM), Personal Knowledge Management (PKM) and Information Literacy (IL). Following the presentation at QQML 2012 (Limerick, Ireland) of the theoretical basis and the results of the first part of PKIM studies, its second part is described in this paper. The subject of these studies are PKIM behaviour, which is a type of knowledge and information behaviour; and related attitudes, skills and feelings of individuals. Qualitative and quantitative methods were used. The respondents’ group consisted of 510 Information Science and Library Studies students from nine universities throughout Poland.